Spectres of Today: The Fractures of History in “Horse Money” (2014) - Branco, Sérgio Dias (2020)
It took Pedro Costa four feature films to get to “Horse Money” (“Cavalo Dinheiro”, 2014). In Down to Earth (Casa de Lava, 1994), a Portuguese nurse accompanies an immigrant worker in coma from Lisbon to his homeland, the Cape Verdean island of Fogo. “Bones” (“Ossos”, 1997), In “Vanda’s Room” (“No Quarto da Vanda”, 2000), and “Colossal Youth” (“Juventude em Marcha”, 2006) form a trilogy in which a group of Cape Verdean immigrants who lived in the Fontainhas slum becomes central. First travelling to Cape Verde, then getting to know and working with people from that Portuguese ex-colony on the outskirts of Lisbon, Costa’s films respond to the need for the voices of those who have been subordinated — the colonised, the discriminated, the exploited — to be articulated and valued. This article analyses the film style of “Horse Money”. It also pays attention to its thematic concerns and connections with other films directed by Costa, particularly those with Ventura, the central character in “Horse Money”. It argues that “Horse Money” tackles spectres haunting contemporary Portuguese society in a radical way, both politically and aesthetically. Its politics of representation are connected with the composition of a fractured history. These fractures emerge from the liberation of Cape Verde from Portuguese colonial domination as well as from the conflicting ruptures and continuities after the 1974 Carnation Revolution. In line with such an approach to these themes, the use of digital video, which has become common in Costa’s cinema since In Vanda’s Room, achieves hauntingly expressive qualities through mise-en-scène and image modulation.